INSPECTING A BUMP TEST IN THE MAINTENANCE OF A 1200-CC DAIHATSU SIGRA DISC BRAKE - Subekti Subekti; Abdul Hamid; Basuki Dwi Effendy; Agung Wahyudi Biantoro (Universitas Mercu Buana, 2019)
A motorized vehicle needs a system that can not only reduce the speed and stop the vehicle but can also serve as a safety tool and ensure a safe distribution which is called a braking system. It is important to conduct maintenance of a disc brake that is part of the braking system. Therefore, this study developed a technique to inspect a 1200-cc Daihatsu Sigra disc brake through the vibration measurement using a bump test. A disc brake is comprised of three fields: A (located next to the center of the disc brake), B ( in the middle diameter), and C ( in the outer diameter of the disc brake). Each field has ten measurement points. This study showed that disc brake damages occurring in field A were at points 1-3, and they appeared after the 250-Hz frequency. Meanwhile, in fields B and C, at all measurement points, there were no changes taking place at any frequency.